Public Financial Transparency and Accountability: A Normative Analysis of International Reporting Standards - Mahfud Heru Fatoni; Diana Widhi Rachmawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study offers a normative–conceptual analysis of public financial transparency and accountability under international reporting standards. Drawing on public-sector accounting theory, regulatory governance, and political economy perspectives, it critically examines how transnational standard-setting regimes structure informational transparency, institutional answerability, and distributive consequences. A structured review of peer-reviewed scholarship and authoritative regulatory documents forms the analytical corpus, enabling thematic coding of dominant normative premises and embedded assumptions concerning materiality, stakeholder hierarchy, and public value. The findings identify a persistent tension between investor-oriented materiality constructs and broader democratic accountability claims, particularly in the context of accrual-based reforms and expanding sustainability disclosure frameworks. The analysis further demonstrates that transparency effects depend on enforcement capacity, institutional coherence, and alignment with domestic governance infrastructures rather than on formal adoption alone. By synthesizing doctrinal analysis with accountability theory, the article develops an integrated evaluative framework for assessing whether international reporting standards substantively strengthen public financial transparency or primarily institutionalize compliance within global regulatory architectures.